Smart Crop-Field Monitoring and Irrigation System Based On IoT (International Journal of Innovative Research in Computer Science & Technology, 2021)
Agriculture is critical to the growth of  agrarian countries like India. Agriculture-related issues  have long been a roadblock to the country's growth.  Smart agriculture, which involves updating existing  agricultural techniques, is the only answer to this issue.  As a result, the suggested approach seeks to use  automation and IoT technology to make agriculture  smart. Crop growth monitoring and selection, irrigation  decision assistance, and other applications are enabled by  the Internet of Things (IoT). To modernize and increase  agricultural production, a Microcontroller Pi-based IoT  watering solution is recommended. The major purpose of  this research is to grow crops with the least amount of  water possible. Most farmers spend hours throughout the  fields in order to focus on groundwater resources to  plants at the proper time. Groundwater contamination  should be enhanced, and the complexity of the system  circuit should be reduced. The protocol determines the  quantity of water necessary analysis of the results  obtained from the sensors. Six sensors detect the  temperature of the food of the soil, but also the  precipitation, temperatures, and duration of daylight each  day, and send the data to the mobile node. Dependent on  these characteristics, the proposed systems must calculate  the quantity of water needed for irrigation. The usage of  Crop Monitoring (PA) with virtualization is the system's  key advantage, as it will evaluate and use of water  nitrates while boosting crop yields and aid in analyzing  field condition.
Keywords: Precision Agriculture Irrigation system; IOT; Raspberry-pi; cloud computing